(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
National Anthem – (Greek. Humnos – hymn, solemn song) is a poetic and musical work glorifying the Motherland, the state, historical events, their heroes, one of the symbols of the state. The national anthem is a formal song that is performed at official state ceremonies, holiday celebrations, state delegations, welcoming and observing guests. When the national anthem is played, all participants stand up. Soldiers stand with their hands on their temples (“chest”), citizens take off their hats and listen with their hands on their chests